Social Media Influencers on Facebook and Their Impact on Consumers - Nova, Janifar Kamal (Institut Teknologi Sepuluh Nopember, 2023)
This study aims to pinpoint the elements contributing to social media influencers' (SMIs) popularity and effectiveness in Bangladesh. Additionally, the study aims to determine how these influencers impact consumers' purchasing decisions. The study employs a quantitative research approach, utilizing an online survey questionnaire. The survey involved 208 participants who follow at least one social media influencer on Facebook, selected through a random sampling technique. The study's results highlight that positive reviews and feedback from other followers/consumers are the most potent factors in creating trust towards SMIs. Additionally, the quality of content and SMI's expertise and knowledge in a specific field/topic matter most to create an audience base. Besides, most followers believe that expertise attracts them to SMIs; hence, SMIs should not promote anything they do not know much about, representing their trustworthiness and transparency to the followers. Also, the recommendation of SMIs and these consumer-trust-building characteristics are associated. Brands choose SMIs to convey their message to the targeted audience; the findings also reveal that influencers significantly influence consumers' purchasing decisions through their recommendations, and age is one of the independent variables that is associated with the recommendations of SMIs